Pelatihan Kepada Orang Tua dalam Mengajar Anak Menulis Menggunakan Buku “Smart Writting” - Dini Ramadhani; Nuryanis Nuryanis; Sukirno . (LPPM UNINUS, 2017)
Dedication to society is done because of the lack of parents knowledge who have early childhood in writing teaching in Gampong Meurandeh Dayah. There are still many children in elementary school who have not been fluent in writing. This dedication aims to provide knowledge about the development stages of writing skills and how to teach writing in early childhood to parents. Problem solved by 3 methods of presentation, demonstration, and practice. Presentation of explaining materials the developmental stages of early childhood writing and distributing the book